Current status and development prospects of aquatic vaccines - Du, Yang; Hu, Xiaoman; Miao, Liang; Chen, Jiong (Frontiers in Immunology, 2022)
Aquaculture diseases are a significant barrier to the industry's sustainable and healthy growth. The aquaculture business is suffering significant financial losses as a result of the worsening water quality and rising frequency of aquatic disease outbreaks brought on by the expansion of aquaculture. Drug control, immunoprophylaxis, ecological integrated control, etc. are the principal control strategies for fish infections. For a long time, the prevention and control of aquatic diseases have mainly relied on the use of various antibiotics and chemical drugs. However, long-term use of chemical inputs not only increases pathogenic bacteria resistance but also damages the fish and aquaculture environments, resulting in drug residues in aquatic products, and severely impeding the development the of aquaculture industry. The development and use of aquatic vaccines are the safest and most effective ways to prevent aquatic animal diseases and preserve the health and sustainability of aquaculture. To give references for the development and implementation of aquatic vaccines, this study reviews the development history, types, inoculation techniques, mechanisms of action, development prospects, and challenges encountered with aquatic vaccines.